Thin-Walled Steel Stiffened Square Box Columns with Uniform and Graded Thickness under Bidirectional Cyclic Loading. (15th September 2020) - Al-Kaseasbeh, Qusay; Mamaghani, Iraj H.P.
Highlights: The BGB column with size and volume of material equivalent to BB column is proposed. The behavior of BB and BGB columns is investigated. The BGB column is proved to have significant improvements in strength, ductility, and post-buckling. Hysteretic behavior of columns under unidirectional loading is over-simplified and leads to over-estimated strength and ductility capacity. Proposed formulae for strength and ductility of the BB and BGB columns are given. Abstract: In this paper, the overall hysteretic behavior of uniform (BB) and proposed graded-thickness (BGB) thin-walled steel square box columns under constant axial force and circular bidirectional cyclic lateral loading is investigated. First of all, the adopted finite element model (FEM) in ABAQUS is verified with the experimental results in the literature and employed for the analysis. Second, the proposed BGB column, with the same cross-section size and volume of material equivalent to the BB column, is evaluated. Then, the strength and ductility deterioration of both BB and BGB columns under circular bidirectional cyclic loading path over the unidirectional path are emphasized. Finally, an intensive parametric study is conducted to investigate the effect of main design parameters including: width-to-thickness ratio parameter ( Rf ), column slenderness ratio parameter ( λ ), magnitude of axial load ( P/Py ), and number of loading cycles ( N ) on the overall hysteretic behavior of BB and BGB columns under constant axial force and circular bidirectional cyclic lateral loading. Subsequently, design formulae have been derived to predict the ultimate strength and ductility capacities of the BB and BGB columns.